A Sustainable Redox‐Flow Battery with an Aluminum‐Based, Deep‐Eutectic‐Solvent Anolyte. (30th May 2017) - Zhang, Changkun; Ding, Yu; Zhang, Leyuan; Wang, Xuelan; Zhao, Yu; Zhang, Xiaohong; Yu, Guihua
Abstract: Nonaqueous redox‐flow batteries are an emerging energy storage technology for grid storage systems, but the development of anolytes has lagged far behind that of catholytes due to the major limitations of the redox species, which exhibit relatively low solubility and inadequate redox potentials. Herein, an aluminum‐based deep‐eutectic‐solvent is investigated as an anolyte for redox‐flow batteries. The aluminum‐based deep‐eutectic solvent demonstrated a significantly enhanced concentration of circa 3.2 m in the anolyte and a relatively low redox potential of 2.2 V vs. Li + /Li. The electrochemical measurements highlight that a reversible volumetric capacity of 145 Ah L −1 and an energy density of 189 Wh L −1 or 165 Wh kg −1 have been achieved when coupled with a I3 − /I − catholyte. The prototype cell has also been extended to the use of a Br2 ‐based catholyte, exhibiting a higher cell voltage with a theoretical energy density of over 200 Wh L −1 . The synergy of highly abundant, dendrite‐free, multi‐electron‐reaction aluminum anodes and environmentally benign deep‐eutectic‐solvent anolytes reveals great potential towards cost‐effective, sustainable redox‐flow batteries.